2017
DOI: 10.15632/jtam-pl.55.1.317
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of droplet formation in a Y-junction microchannel

Abstract: This study investigates the formation process of droplets in a Y-junction microchannel using two immiscible fluids: water as the continuous fluid and oil as the dispersed phase. We have examined the influence of the capillary number, flow rate ratio and viscosity ratio between the two fluids; parameters which determine the length and generation frequency of the droplets. Numerical simulations have been performed using the software Ansys Fluent with the interface capture method Volume of Fluid (VOF) for solving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Analyses between SIMPLE, SIMPLEC, and PISO shemes have shown that the PISO scheme is the most suitable scheme for multiphase flows. Compared to the other schemes, PISO is more robust and predicts accurate results (Lamine Diouf & Romero, 2017). Moreover, PISO has been previously used for simulations of droplet formation (Chaves, Duarte, Coltro, & Santos, 2020;Ren & Leung, 2016;Wang et al, 2018).…”
Section: Solution Methodsmentioning
confidence: 99%
“…Analyses between SIMPLE, SIMPLEC, and PISO shemes have shown that the PISO scheme is the most suitable scheme for multiphase flows. Compared to the other schemes, PISO is more robust and predicts accurate results (Lamine Diouf & Romero, 2017). Moreover, PISO has been previously used for simulations of droplet formation (Chaves, Duarte, Coltro, & Santos, 2020;Ren & Leung, 2016;Wang et al, 2018).…”
Section: Solution Methodsmentioning
confidence: 99%